2017
DOI: 10.1007/s00335-017-9678-7
|View full text |Cite|
|
Sign up to set email alerts
|

The Valdostana goat: a genome-wide investigation of the distinctiveness of its selective sweep regions

Abstract: The Valdostana goat is an alpine breed, raised only in the northern Italian region of the Aosta Valley. This breed's main purpose is to produce milk and meat, but is peculiar for its involvement in the "Batailles de Chèvres," a recent tradition of non-cruel fight tournaments. At both the genetic and genomic levels, only a very limited number of studies have been performed with this breed and there are no studies about the genomic signatures left by selection. In this work, 24 unrelated Valdostana animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
(45 reference statements)
3
19
2
1
Order By: Relevance
“…Moreover, the selection signatures found in our study do not display classic hard sweep characteristics, which is to be expected for complex traits. This is in contrast to the findings with Valdostana goats in Italy ( Talenti et al, 2017 ). This may arise due to the very diverse nature of the populations and absence of hard and long selection signature regions observed within the populations at the 50K SNP marker density.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the selection signatures found in our study do not display classic hard sweep characteristics, which is to be expected for complex traits. This is in contrast to the findings with Valdostana goats in Italy ( Talenti et al, 2017 ). This may arise due to the very diverse nature of the populations and absence of hard and long selection signature regions observed within the populations at the 50K SNP marker density.…”
Section: Discussioncontrasting
confidence: 99%
“…This may arise due to the very diverse nature of the populations and absence of hard and long selection signature regions observed within the populations at the 50K SNP marker density. Second, our study pooled genotypes from six different breeds and lending to picking out differences between the breeds, unlike in the study of Talenti et al (2017) , whose focus was on only one breed.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that this increase in homozygosity would be consistent with selection for mutations affecting fat-tail size several thousand years following domestication. Therefore, although the existence of ROH islands has been attributed to several factors (recombination events, demography) [42], our results corroborate the hypothesis that regions of high-homozygosity may indeed harbor targets of positive selection, as also observed in previous studies [20,22,43].…”
Section: Discussionsupporting
confidence: 91%
“…Another method for detecting signatures of positive selection based on intra-population analysis is the identification of high-homozygosity regions [6]. Since ROHs are normally abundant in regions under positive selection, their accumulation at specific loci, or islands, has been used to identify genomic regions that reflect directional selection in cattle [19], sheep [20], horse [21] and goat [22]. We therefore checked if such regions of high-homozygosity overlapped with putative selection signatures in the sheep breeds considered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the selection signatures found in our study do not display classic hard sweep characteristics, which is to be expected for complex traits. This is in contrast to the findings with Valdostana goats in Italy (Talenti et al, 2017), This may arise due to the very diverse nature of the populations and absence of hard and long selection signature regions observed within the populations at the 50K SNP marker density. Secondly, our study pooled genotypes from six different breeds and lending to picking out differences between the breeds, unlike in the study of Talenti and colleagues (Talenti et al, 2017), whose focus was on only one breed.…”
Section: Selection Signaturescontrasting
confidence: 99%